Which Structure (diségno, 2026)
Research and applications of graphic representation largely concern the ‘design’ of form. Form is, in fact, the powerful reference, the attractor toward which the processes of knowledge acquisition and design generation tend to converge. Research and applications on the structure instead, which nevertheless supports the form, is sometimes less evident, either because it is somehow taken for granted and considered less relevant than the corresponding formal outcomes, or because it remains hidden behind a certain intellectual secrecy, not always naive. The topic of codes, methods, and tools adopted in the work on the structure, therefore offers an interesting frame for further explorations.But which structure? [read more]